Thailand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper reviews the aggregate balance-sheet analysis that describes the improvement in Thailand's overall balance sheet since the crisis, and also highlights the potential vulnerabilities. It assesses the public debt and contingent liabilities, and developments in the banking sector. It discusses the operations of Specialized Financial Institutions and related regulatory issues, the financial and corporate sector restructuring, and also presents an overview of developments in nonperforming loans and assets. It reviews the growth without credit feature of Thailand, which explains how firms have financed their operations after the crisis.